Bridging Tradition and Education: Integrating Indigenous Games into School and Higher Education Curricula Under NEP 2020 - Tanveer Ahmed Dar; Archana S. Giri (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
The National Education Policy (NEP) 2020 marks a transformative shift toward holistic, experiential, and culturally rooted education in India. It explicitly advocates integrating indigenous and traditional games into school and higher education curricula to foster physical fitness, cognitive growth, social skills, teamwork, cultural identity, and lifelong health and well-being (Para 4.8 on sports-integration). Games such as Kabaddi, Kho-Kho, Mallakhamb, Gilli-Danda, Seven Stones, Gatka, Kalaripayattu, and various tribal and regional variants carry profound historical and cultural significance. However, rapid urbanization, digital distractions, and standardized academic priorities have marginalized their inclusion in formal education.This study examines the alignment of indigenous games with NEP 2020's key pillars, including sports-integrated learning, Indian Knowledge Systems (IKS), and multimodal pedagogy. It highlights multifaceted benefits: enhanced motor skills, emotional resilience, environmental awareness, intergenerational bonding, and national unity through cultural preservation. Drawing on policy analysis, case studies of post-NEP initiatives (e.g., NCERT's Khel Yatra textbook series for Classes 6–8 incorporating state-specific games, Odisha's revival of 75 traditional games, and Fit India Movement efforts), and stakeholder perspectives, the paper proposes practical integration models across school stages and higher education. These include teacher training programs, infrastructure enhancements, and context-sensitive assessment frameworks. Findings indicate that indigenous games revitalize cultural heritage while creating inclusive, engaging, and sustainable learning environments. Recommendations emphasize mandatory inclusion policies, community participation, and longitudinal evaluations to assess student outcomes. This approach advances NEP 2020's vision of an education system deeply rooted in Indian heritage, equipping learners to address contemporary challenges effectively.